Philosophical Foundation of Islamic Education in Muhammad Iqbal's Asrar-i Khudi: An Ontological, Epistemological, and Axiological Analysis - Zahira Jannataini; Jamali Jamali; Sumanta Sumanta (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
This study explores the philosophical foundations of Islamic education as articulated in Muhammad Iqbal’s seminal work Asrar-i Khudi, focusing on ontological, epistemological, and axiological dimensions. The research aims to reconstruct Iqbal’s ideal concept of Islamic education and examine how his philosophical poetry provides a normative framework for spiritual and intellectual development. Adopting a qualitative, text-based hermeneutic approach, this study analyzes seven poems in Asrar-i Khudi that explicitly address educational values and concepts. The findings reveal that ontologically, Iqbal envisions education as a process of realizing the self (khudi) in harmony with divine reality; epistemologically, he emphasizes critical reasoning, dynamic ijtihad, and knowledge integration; and axiologically, he advocates ethical responsibility and moral autonomy as essential educational goals. These results suggest that Iqbal’s educational philosophy offers a transformative paradigm that bridges metaphysical depth with practical human development. This study contributes to the discourse on Islamic educational thought by providing a conceptual model grounded in classical philosophy yet responsive to contemporary challenges in Muslim societies.